Expert System Using Certainty Factor Method For Adjustment Of Learning Styles With Students - I Putu Aris Sanjaya; I Gede Aris Gunadi; Gede Indrawan (Information Technology and Science (ITScience), 2023)
Alignment of students with learning styles greatly affects the quality of learning of students in educational units. With good learning quality, the passing rate of students in an educational unit will also increase and can produce quality graduates. So far, the learning process implemented in this school has been going well when viewed based on the number of students graduating with the number of students present, but so far no further research has been conducted regarding this suitability so that the effectiveness of student learning is still not optimal. Based on this, the research objective is to build an Expert System with the Certainty Factor method to adjust the learning styles of students at SMK PGRI 5 Denpasar. Based on the results that will be obtained through the system designed and built in this research, it is hoped that it will make it easier for educators to prepare learning models and strategies that will be given to students from the results of determining student learning styles. The research results obtained from the test results show 100% suitability in giving dominant results to students' learning styles. In this study the students who were used as the test sample had different learning style percentage accuracy so that it could be used to determine the right learning style for each student.